Development of interfacial stress during selective laser melting of TiC reinforced TiAl composites: Influence of geometric feature of reinforcement. (5th November 2018) - Ma, Chenglong; Gu, Dongdong; Dai, Donghua; Zhang, Hongmei; Du, Lei; Zhang, Han
Abstract: In this work, interfacial stress evolution behavior of TiC reinforced TiAl composites fabricated by selective laser melting were investigated, based on a meso-scale finite element model solely including a single reinforcing particle. The results implied that stress concentration always emerged where the maximum temperature gradient existed. As the laser beam successively moving from the left side of powder bed to the right side, the matrix around TiC particle underwent a solid-to-liquid-to-solid transfer process, as a result of which the interface located at left side and right side of TiC particle experienced a transformation from a compressive stress to a tensile stress. But the top edge of TiC particle always suffered from the tensile stress. Two different types of reinforced particle, namely sphere-shaped particle and cubic particle, were analyzed in this work. For the sphere-shaped one, the calculated plastic flow stress in the interface was higher than the corresponding simulated Von Mise stress during the solidifying period, while the opposite result was obtained for the cubic one. It indicated that higher thermal shock resistance could be obtained for sphere-shaped TiC reinforced composites which was further verified by the experiment results. Graphical abstract: Unlabelled Image Highlights: A meso-scale thermal-stress coupling model of SLM fabricated TiC/TiAl composites was established. Stress development in the interface between TiC particle and the TiAl matrix was illuminated. Higher thermal shocking resistance was achieved when using sphere-shaped reinforcement.